EP446 When can we suspect gynecological lymphomas? Ultrasound features of ovarian and uterine lymphomas, a single-center experience. (1st November 2019) - Boussedra, S; Giunchi, S; Perrone, AM; De Leo, A; Tesei, M; De Iaco, P
Abstract : Introduction/Background: Lymphomas involving the gynecologic tract are uncommon and may occur as de novo or secondary as a part of systematic disease. Among gynecological lymphomas, the ovary is the most common anatomic site, accounting for 1.5% of ovarian neoplasm. Involvement of the cervix is more frequent than the uterine body and accounts for less than 1% of extranodal lymphomas. The aim of our study is to improve the use of ultrasound to detect or suspect promptly ovarian and uterine lymphoma through our experience. Methodology: Patients with histological diagnosis of ovarian and uterine lymphomas, from 2011 to 2018, were retrospectively recruited from the database of our Gynecological Oncology Unit. The sonographic reports and digital images were analyzed, recording specific features. Results: We recruited seven patients. Five out of seven (71%) of them had ovarian lymphoma, two of them had uterine lymphoma (29%).The echotexture of all the masses had a follicular architecture, reminding the nodular-appearing proliferation in the histology. Median age of the patients was 40 years (range 12–71). All the lymphomas appeared as hypoechoic, without cones of shadows and calcification; lymphomas were discretely solid masses in 5/7 (71%) (median diameter 71 mm, range 26–103 mm), borders were well defined in all the ovarian lymphoma, and shaded in all uterine lymphoma. Internal cystic lacunae were in 3/7 (43%). Vascularisation was moderate in 3/7 cases (43%), and strong in 4/7 (57%), with an evidence of a lead vessel in 5/7 cases (71%). Conclusion: Ovarian and uterine solid lesions with heterogeneous nodular echogenicity, follicular architecture, rich in vascularization and presence of lead vessel, should be suspected of being lymphoma. Disclosure: Nothing to disclose.